Valdosta State Sport History, book 1 Baseball, vol 2: 1955-1977 "The Players" - (:unkn) unknown (My University, 2012)
Newspaper clipping and player stats from 1955-1977. Volume 2 of 2.
Keywords: baseball; Sports history; Blazers; the players